2014
DOI: 10.1364/oe.22.012545
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured gradient-index antireflective coating fabricated on a fiber tip with direct laser writing

Abstract: We present a simple broadband gradient-index antireflective coating, fabricated directly on a single mode telecom fiber tip. A regular array of hemi-ellipsoidal protrusions significantly reduce the Fresnel reflection from the glass-air interface. The parameters of the structure were optimized with numerical simulation for the best performance at and around 1550 nm and the coating was fabricated with Direct Laser Writing. The measured reflectance decreased by a factor of 30 at 1550 nm and was below 0.28% for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The effective refractive index of the structure can be modified by changing the free parameters: height h and spacing d. In our work, the geometry of the structure was optimized by finding the minimum of the back-reflectivity for the single mode SMF-28 fibre at 1550 nm. Details of the design procedure, fabrication and measurements can be found in [11].…”
Section: Dlw On a Fibre Tip: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective refractive index of the structure can be modified by changing the free parameters: height h and spacing d. In our work, the geometry of the structure was optimized by finding the minimum of the back-reflectivity for the single mode SMF-28 fibre at 1550 nm. Details of the design procedure, fabrication and measurements can be found in [11].…”
Section: Dlw On a Fibre Tip: Resultsmentioning
confidence: 99%
“…Moreover, the uncompensated fibre tilt can affect the quality of the structure, as the height of the single hemiellipsoids will not be constant. Nevertheless, it was shown that the height of the structure is not a critical parameter, so this can act as efficient AR coating even when there are significant discrepancies from the designed geometry [11]. Figure 9 shows an example of the fibre-integrated AR coating.…”
Section: Dlw On a Fibre Tip: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore tempting to fabricate the LMRG directly on cleaved or polished fibre facets. Several technologies were examined for micromachining of fibre facets such as interference lithography (Yang et al 2012), photolithography (Johnson et al 2003), electron-beam lithography , focused ion-beam milling (Schiappelli et al 2004;Vanek et al 2016), stamping (Sanghera et al 2010;MacLeod et al 2011), nano-imprint technology (Kostovski et al 2009;Kanamori et al 2013), two-photon polymerization 3D printing (Williams et al 2011;Gissibl et al 2016a, b), direct laser writing (Kowalczyk et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…This allows fundamentally unlimited integration and packaging of diverse functional microdevices. [42][43][44][45][46][47][48][49][50] It should be mentioned that such structures can serve as 3D templates for infiltration of another media with desired properties which cannot be nanofabricated in 3D by DLW. [51][52][53] Lastly, usage of ultrashort pulses enables avoidance of photosensitization [54][55][56] which is an arising issue and might be limiting factor to optical and biological applications due to its light absorption and toxicity.…”
Section: Introductionmentioning
confidence: 99%